Ang bagong Salamyan reviving the Marikina footwear industry through an image-generative third place Marikina Shoe Complex - Caranto, Dominique-Anne B.
Deeply embedded in Marikina's identity and heritage, the city's footwear industry struggles to compete with the dominant mass-produced imports and impose itself upon the market. This study investigates how architecture can invigorate the industry by proposing a Marikina Shoe Complex situated within Marikina River Park and composed of a shopping center and a footwear manufacturing hub. This design is deeply-rooted on the concept of "genius loci'" emphasizing the Marikina shophouse along with other components of the built environment which has contributed to the growth and survival of the industry. Apart from its heritage structures, strategies to incorporate the industry's emerging image especially amidst online platforms such as Instagram was thoroughly considered. Furthermore, the design will introduce spatial strategies to encourage collaboration among designers and shoemakers within the industry while providing them with a space to innovate. Lastly, an "experiential customer journey map" will be developed to engage visitors and elevate their perception of Marikina footwear. Thus, this research envisions a sustainable, collaborative, and ever-evolving commercial complex that integrates its manufacturing aspect into the concept of a "third place." Ang Bagong Salamyaan, the physical embodiment of this third space, represents the revival of the traditional Marikina concept of "salamyaan" and how its concept rooted in Marikina can inform the design of a 'third place" that will not only promote the sale and creation of Marikina footwear, but also serve as an attractive social gathering place for Marikenos.